Energy absorption properties of thin-walled square tube with lateral piecewise variable thickness under axial crashing. Issue 8 (7th October 2019) - Liu, Shutian; Ding, Xueshan; Tong, Zeqi
Abstract : Purpose: This paper aims to study the energy absorption properties of the thin-walled square tube with lateral piecewise variable thickness under axial crashing and the influence of the tube parameters on energy absorption. Design/methodology/approach: In this work, the energy absorption properties of the thin-walled square tube were analyzed by theoretical, numerical and experimental approach. The numerical results are obtained based on the finite element method. The explicit formulation for predicting the mean crushing force of the tube with lateral piecewise variable thickness was derived based on Super Folding Element method. The limitation of the prediction formulation was analyzed by numerical calculation. The numerical calculation was also used to compare the energy absorption between the tube with lateral piecewise variable thickness and other tubes, and to carry out the parametric analysis. Findings: Results indicate that the thin-walled tube with lateral piecewise variable thickness has higher energy absorption properties than the uniform thickness tubes and the tubes with lateral linear variable thickness. The thickness of the corner is the key factor for the energy absorption of the tubes. The thickness of the non-corner region is the secondary factor. Increasing the corner thickness and decreasing the non-corner thickness can make the energy absorption improved. It is also found that the prediction formulation of the mean crushing force given in this paper can quickly and accurately predict the energy absorption of the square tube. Originality/value: The outcome of the present research provides a design idea to improve the energy absorption of thin-walled tube by designing cross-section thickness and gives an explicit formulation for predicting the mean crushing force quickly and accurately.